(untitled) (Fiep Bulletin - online, 2013)
Junior Company is a company comprised exclusively by undergraduate students who, whereby, perform projects and provide services in their respective areas. With educational purposes, the junior company may be seen by undergraduate students as a huge and perhaps the unique opportunity to apply the knowledge of their course as a student. Founded in 1998, the junior company of Physical Education - EFICAP of the Federal University of Viçosa (UFV) currently offers opportunities in projects of different areas of Physical Education. This study aimed to analyze, through different studies, the influence of EFICAP in academic formation of the undergraduate students of Physical Education at UFV. It has been established a relationship between existing studies and, from the results, it was concluded that the junior company has not exercised the expected influence in the academic formation of these students; according to the methodology used by the author, it was observed that the difference of the presence of entrepreneurial characteristics among students connected directly, indirectly and unrelated to the company is not relevant. It may be noticed also, in another study that, the level of entrepreneurial characteristics in students in general, regardless of being or not a member of the junior company, was less than expected. It is concluded that there is a necessity to make the undergraduate students aware concerning the importance and/or the entrepreneurial characteristics, since it is observed, through the program course, the lack of obligatory disciplines; it is also necessary that the Higher Education Institutions offer new tools to encourage entrepreneurship, as well as incentive and conditions for junior companies, in general, actually to become a laboratory that will contribute to the development of these characteristics.